The 8051 microcontroller - MacKenzie, I. Scott (Prentice Hall, 1999)
Beginning at a rudimentary level and progressing to advanced concepts and finished design examples, this introduction to microcontrollers emphasizes architecture and programming (rather than electrical details) and explores the hardware and software features of the MCS-51 family of microcontrollers specifically. Discusses software topics in the context of Intel's assembler (ASM51) and linker/locator (RL5 1) and the object-to-hex conversion utility (OH). Offers thorough discussion of the 8051 10-chip - the serial-port, timers, and interrupts. Provides easy-to-follow, incremental instruction in the 8051 instruction set, with annotated examples of programs, assembler operations, and linker operations. Discusses advanced programming methods - e.g., a variety of structured programming structures, pseudo code, and assembly language programming style. Features an easy-to-build computer project - with a chip-by-chip description and schematic for building the 10-chip single-board SBC-51 computer. Offers a listing of an 8051 monitor program (MON51) - with complete documentation. Includes manufacturer's data sheet and instruction set definitions. For practicing electronics technicians or engineers interested in learning about microcontrollers.